The Clinical Values of Insulin-Like Growth Factor-1 and Insulin-Like Growth Factor Binding Protein-3 Levels in Blood and Thyroid Nodules. (7th September 2017) - Altas, Ayfer; Kuzu, Fatih; Arpaci, Dilek; Unal, Mustafa; Can, Murat; Barut, Figen; Kokturk, Furuzan; Ilikhan, Sevil Uygun; Bayraktaroglu, Taner
Abstract : Aim. Insulin-like growth factor-1 (IGF-1) is a potent mitogen for many cells. IGF-1 plays a role in the pathogenesis of various tumors with its mutagenic and antiapoptotic properties. The aim of this study was to determine both the serum and intranodular levels of IGF-1 and insulin-like growth factor binding protein-3 (IGFBP-3) in patients with nodular thyroid diseases. Materials and Methods. In this study, 80 subjects who performed fine-needle aspiration biopsy (FNAB) were required in order to investigate the effects of serum and intranodular IGF-1 and IGFBP-3 in the pathogenesis of nodules. After performing FNAB, IGF-1 and IGFBP-3 levels were determined in blood and aspiration samples. Results. The serum levels of IGF-1 (232.8 ± 12.9 ng/ml) and IGFBP-3 (4.8  μ g/ml) were found significantly higher than that of the intranodular IGF-1 (39.1 ng/ml) and intranodular IGFBP-3 levels (0.173  μ g/ml) (p < 0.01 ). Intranodular levels of IGF-1 and IGFBP-3 were higher in subjects with multinodular thyroid gland than those of subjects with solitary nodules (p = 0.043 ). A positive correlation between the nodule size and the serum IGFBP-3 levels was detected (p = 0.042, r = 0.23 ). Conclusion. This study demonstrated the possible role of both IGF-1 and IGFBP-3 in the growth and the formation of multinodularity of thyroid nodules.